Pembangunan dan Implementasi Website Profil Kelurahan Tanah Lapang, Kecamatan Lembah Segar, Kota Sawahlunto - Jefril Rahmadoni; Husnil Kamil; Wahyudi Wahyudi; Nedia Putri Ismala; Ahmad Fadli Ramadhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The use of information technology has resulted in numerous life changes. Starting with manual work to ensure that knowledge of innovation grows, creating automated or digital work makes it easier for people to carry out their daily operational activities. A website is an information medium to introduce or promote a company or organization. Develop a profile website to aid in information dissemination and tools for village leaders that can be accessed more quickly and practically, resulting in an innovative, effective, and efficient teaching and learning process. Nowadays, technology allows all manual labour to be converted into a practical digital mode. This community service project aims to help the Tanah Lapang Village socialize and the village head with responsibilities. The executors were a group of lecturers and students from Andalas University's Faculty of Information Technology. The stages of creating a website began with identifying the village's problems. Tanah Lapang Village information is now available on the website, including its profiles, history, organizational structure, population data, facilities, and tourism activities in the village.